India's exports of food products: Food safety related issues and way forward - Tanu M. Goyal; Arpita Mukherjee; Avantika Kapoor (Indian Council for Research on International Economic Relations (ICRIER), 2017)
Since independence, India has come a long way from being a food-deficit to a food surplus country. With its varied agro-climatic conditions and large production base, the country has become a leading exporter of fresh and processed food products. The Indian government is keen to promote exports of fresh and processed food products and, in recent years, the government has come up with several reforms and schemes to support exports. The Indian government is also undertaking policies and schemes for supporting sustainable agriculture practices and is encouraging organic farming. Despite these efforts, Indian exporters of agricultural products continue to face rejections and bans in key markets and most of these are related to non-compliance with food safety and health standards. Such non-compliance is because of several reasons including pest infestations, presence of chemical residues that are banned by the importing country's national food law, higher than maximum approved levels of chemical residue and food contamination due to germination of bacteria. Rejection and/or bans have not only led to loss of income for exporters, farmers and processors, but also loss of market to exporters from other developing countries who are able to meet the food safety and health standards of importing countries. Given this background, this study, based on secondary information analysis and a primary survey, tries to identify the food safety barriers that Indian exports face in key export markets, the reasons for such barriers and the impact of these on exporters and farmers. Based on the survey findings, the study lists three key strategies to address these barriers. These include (a) implementing domestic reforms (b) bilateral discussions with trading partners, mutual collaborations and knowledge sharing, addressing the issue through mutual recognition in bilateral trade agreements, etc., and (c) raising the issue in multilateral forums such as the WTO.
Keywords: Q17; Q18; F13; C83; 330; food safety; food products; sanitary and phytosanitary; export; India; World Trade Organization